2020
DOI: 10.1055/s-0040-1708832
|View full text |Cite
|
Sign up to set email alerts
|

Using Rheo-Small-Angle Neutron Scattering to Understand How Functionalised Dipeptides Form Gels

Abstract: We explore the use of rheo-small-angle neutron scattering as a method to collect structural information from neutron scattering simultaneously with rheology to understand how low-molecular-weight hydrogels form and behave under shear. We examine three different gelling hydrogel systems to assess what structures are formed and how these influence the rheology. Furthermore, we probe what is happening to the network during syneresis and why the gels do not recover after an applied strain. All this information is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The low concentration led to gelation only with no evidence of crystallization whereas the high concentration led to rapid gelation followed by a gel-to-crystal transition. At the low concentration of GdL, stable gelation occurred, and as expected from data from related systems, 56 the SAXS scattering intensity increased in intensity over time. The data could be fitted to a flexible cylinder model with a radius which at early time points has a value of 2.9 nm, and which reaches a value of 4 nm after 210 minutes.…”
Section: Resultssupporting
confidence: 75%
“…The low concentration led to gelation only with no evidence of crystallization whereas the high concentration led to rapid gelation followed by a gel-to-crystal transition. At the low concentration of GdL, stable gelation occurred, and as expected from data from related systems, 56 the SAXS scattering intensity increased in intensity over time. The data could be fitted to a flexible cylinder model with a radius which at early time points has a value of 2.9 nm, and which reaches a value of 4 nm after 210 minutes.…”
Section: Resultssupporting
confidence: 75%
“…Previous reports have shown that 6Br2NapAV undergoes syneresis. 43 Syneresis causes the gel network to contract and shrink with time. 44 This is thought to be due to the removal of negative charge from the self-assembled structures, leading to hydrophobic interactions between the neutral fibres.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned previously, 6Br2NapAV has been shown to undergo syneresis with time. 43 This suggests that the gel network may be contracting and expelling water as it grows, causing it to shrink. As the gel does not visibly shrink in size, gel growth must continue in order to maintain its plateau size.…”
Section: Resultsmentioning
confidence: 99%
“…A range of stiff transparent gelators with similarly functionalized dipeptides have been reported. [43,[45][46][47][48][49][50][51][52][53] Using these gelators in conjunction with NDIs would not compromise the water solubility or color of the system. In this approach, a "best of both worlds" could potentially be achieved, but as highlighted in Figure 1, there is a lot to consider in terms of assembly, rather than just mixing the properties.…”
Section: Introductionmentioning
confidence: 99%